2021
DOI: 10.22159/ijap.2021v13i6.42801
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Multitargeted Molecular Docking Analysis of Pyrazole-Condensed Heterocyclics Against Lung Cancer

Abstract: Objective: The significant drawbacks of chemotherapy are that it destroys healthy cells, resulting in adverse effects. Hence, there is a need to adopt new techniques to develop cancer-specific chemicals that target the molecular pathways in a non-toxic fashion. This study aims to screen pyrazole-condensed heterocyclics for their anticancer activities and analyse their enzyme inhibitory potentials EGFR, ALK, VEGFR and TNKS receptors. Methods: The structures of the compounds were confirmed by IR, NMR and Mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Energy, score, and e-model values determined the optimal docked attitude for every ligand. A computer technology known as molecular docking has been utilized for predicting the ligand's binding mechanism and affinity for the target [11]. The docked conformers were tuned depending on the system's total energy [12].…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Energy, score, and e-model values determined the optimal docked attitude for every ligand. A computer technology known as molecular docking has been utilized for predicting the ligand's binding mechanism and affinity for the target [11]. The docked conformers were tuned depending on the system's total energy [12].…”
Section: Molecular Dockingmentioning
confidence: 99%
“…A computer technology known as molecular docking has been utilized for predicting the ligand's binding mechanism and affinity for the target. The docked conformers were tuned depending on the system's total energy [16,17]. The X-ray crystal structure of S. aureus TMK (PDB: 4HLC, resolution: 1.55Å) was chosen for the modelling effort [12].…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Many studies have revealed the anticancer effects of rhodanines over the last few decades [6][7][8][9][10][11]. The five-membered rhodanine ring bearing a Sulphur and Nitrogen at the first and third positions are reported to have significant anticancer activity against different types of cancer, including breast cancer, prostate cancer, colorectal cancer, liver cancer, pancreatic cancer, gastric cancer, lung cancer, renal cancer, and leukaemia [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%